2020
DOI: 10.1073/pnas.2016238117
|View full text |Cite
|
Sign up to set email alerts
|

Satellites can reveal global extent of forced labor in the world’s fishing fleet

Abstract: While forced labor in the world’s fishing fleet has been widely documented, its extent remains unknown. No methods previously existed for remotely identifying individual fishing vessels potentially engaged in these abuses on a global scale. By combining expertise from human rights practitioners and satellite vessel monitoring data, we show that vessels reported to use forced labor behave in systematically different ways from other vessels. We exploit this insight by using machine learning to identify high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Transshipment offenses commonly involve reefer vessels; hence, in 65% of the cases, they do not co-occur with other illegal fishing–related offenses. However, we find here that in 25% of the cases, illegal transshipment is linked to human rights and labor abuse offenses, including through keeping workers longer at sea and preventing them from escaping poor working conditions and/or filing complaints when reaching nearshore or harbors ( 60 63 ). Nearly 20% of transshipment offenses were linked to illegal fishing offenses, by accepting or transshipping illegally caught fish.…”
Section: Resultsmentioning
confidence: 85%
“…Transshipment offenses commonly involve reefer vessels; hence, in 65% of the cases, they do not co-occur with other illegal fishing–related offenses. However, we find here that in 25% of the cases, illegal transshipment is linked to human rights and labor abuse offenses, including through keeping workers longer at sea and preventing them from escaping poor working conditions and/or filing complaints when reaching nearshore or harbors ( 60 63 ). Nearly 20% of transshipment offenses were linked to illegal fishing offenses, by accepting or transshipping illegally caught fish.…”
Section: Resultsmentioning
confidence: 85%
“…In this article, we are focusing on Regional Fisheries Management Organization (RFMOs), which have mandates to manage fisheries at the high seas. A study by McDonald et al (2020) showed that the risk of forced labor is neither solely linked to exclusive economic zones (EEZs) nor high seas, but occurs globally. Moreover, one of the key areas of focus for RFMOs is the problem of illegal, unreported and unregulated (IUU) fishing that has often been linked to forced work and labor abuse on fishing vessels (Marschke and Vandergeest, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, civil society has pursued activities formerly monopolized by the state, like crisis monitoring (Herscher, 2014; Rothe and Shim, 2018). Satellite activism has also detected activities ranging from the razing of Rohingya villages in Myanmar (Human Rights Watch, 2017) to the destruction of mosques in Xinjiang (Ruser et al, 2020) and forced labor in the global fishing fleet (McDonald et al, 2021). As cautioned in Section III, however, the convergence of advocacy and surveillance may be problematic, with NGOs effectively operating as “intelligence agencies” (Aday and Livingston 2009).…”
Section: Practices Of Critical Remote Sensing: Expose Engage Empowermentioning
confidence: 99%